2018
DOI: 10.1017/qua.2018.8
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Saharan dust influence on the strontium isotope ratios on modern trees from the Bahamas and Turks and Caicos Islands

Abstract: We report on strontium (87Sr/86Sr) isotope results from 91 modern trees growing on the Bahamas and Turks and Caicos Islands. The average87Sr/86Sr ratio of 0.709169±0.000010 is consistent with the late Quaternary limestone of the islands and with the modern ocean value. The absence of any detectable influence of87Sr-enriched Saharan dust is notable, given the known contribution of this material to both past and recent soils of the Caribbean. Our results indicate that the impact of Saharan dust to the modern bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 94 publications
1
10
0
Order By: Relevance
“…Saharan dust 87 Sr/ 86 Sr is mostly between 0.715 and 0.718 [76] and thus much higher (more radiogenic) than any of the seawater precipitated carbonate rocks that dominate The Bahamas geology. However, Schulting et al [77] conducted an extensive strontium isotope study of modern trees from The Bahamas and the Turks & Caicos Islands and the data were all within the strontium range of modern seawater (see also [78, 79]). Carbonate rocks naturally contain very high Sr concentrations and apparently, the Saharan dust strontium contribution is not significant enough to affect the strontium isotopic compositions of the local soils and plants.…”
Section: Methods and Materials Of Analysismentioning
confidence: 99%
“…Saharan dust 87 Sr/ 86 Sr is mostly between 0.715 and 0.718 [76] and thus much higher (more radiogenic) than any of the seawater precipitated carbonate rocks that dominate The Bahamas geology. However, Schulting et al [77] conducted an extensive strontium isotope study of modern trees from The Bahamas and the Turks & Caicos Islands and the data were all within the strontium range of modern seawater (see also [78, 79]). Carbonate rocks naturally contain very high Sr concentrations and apparently, the Saharan dust strontium contribution is not significant enough to affect the strontium isotopic compositions of the local soils and plants.…”
Section: Methods and Materials Of Analysismentioning
confidence: 99%
“…The results demonstrated spatial variation in biologically available strontium, supporting their use as an effective tool for provenance studies in Ireland, but they were incomplete in coverage. Therefore, to construct a map of biologically available strontium for Ireland, we collected and analysed a series of georeferenced modern plants, following the strategy of similar studies elsewhere (Evans et al, 2009(Evans et al, , 2010Copeland et al, 2010Copeland et al, , 2011Hartman and Richards, 2014;Laffoon et al, 2012;Schulting et al, 2018). Here, we combine previously published and new measurements on plants within a GIS-based spatial model to create the first baseline of the biologically available strontium isotope ratios for the island of Ireland.…”
Section: Introductionmentioning
confidence: 99%
“…This study provides evidence for a previously unrecognized peccary introduction to Barbados and indicates the presence of this animal on the island in the 17 th or 18 th century. Along with this new record of human-assisted introduction, our results expand bioavailable Sr data for Barbados and contribute to ongoing efforts to map the West Indian Sr isoscape [22, 25, 34, 51, 54, 55, 57]. Further investigation is required to determine the species, timing, source, and number of animals involved in peccary translocation, and the size and persistence of the population on the island.…”
Section: Discussionmentioning
confidence: 65%
“…The degree to which exogenous aerosols influence bioavailable Sr for Barbados thus requires further empirical assessment. Notably, Schulting et al [57] demonstrated an insignificant effect for Saharan dust on bioavailable Sr in the Bahamas, contrary to Bataille et al’s [55] model predictions.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation